Septal GABA and Glutamate Neurons Express RXFP3 mRNA and Depletion of Septal RXFP3 Impaired Spatial Search Strategy and Long-Term Reference Memory in Adult Mice - Haidar, Mouna; Tin, Kimberly; Zhang, Cary; Nategh, Mohsen; Covita, João; Wykes, Alexander D.; Rogers, Jake; Gundlach, Andrew L. (Frontiers in Neuroanatomy, 2019)
Relaxin-3 is a highly conserved neuropeptide abundantly expressed in neurons of the nucleus incertus (NI), which project to nodes of the septohippocampal system (SHS) including the medial septum/diagonal band of Broca (MS/DB) and dorsal hippocampus, as well as to limbic circuits. High densities of the Gi/o-protein-coupled receptor for relaxin-3, known as relaxin-family peptide-3 receptor (RXFP3) are expressed throughout the SHS, further suggesting a role for relaxin-3/RXFP3 signaling in modulating learning and memory processes that occur within these networks. Therefore, this study sought to gain further anatomical and functional insights into relaxin-3/RXFP3 signaling in the mouse MS/DB. Using Cre/LoxP recombination methods, we assessed locomotion, exploratory behavior, and spatial learning and long-term reference memory in adult C57BL/6J Rxfp3loxP/loxP mice with targeted depletion of Rxfp3 in the MS/DB. Following prior injection of an AAV(1/2)-Cre-IRES-eGFP vector into the MS/DB to delete/deplete Rxfp3 mRNA/RXFP3 protein, mice tested in a Morris water maze (MWM) displayed an impairment in allocentric spatial learning during acquisition, as well as an impairment in long-term reference memory on probe day. However, RXFP3-depleted and control mice displayed similar motor activity in a locomotor cell and exploratory behavior in a large open-field (LOF) test. A quantitative characterization using multiplex, fluorescent in situ hybridization (ISH) identified a high level of co-localization of Rxfp3 mRNA and vesicular GABA transporter (vGAT) mRNA in MS and DB neurons ( 87% and 95% co-expression, respectively). Rxfp3 mRNA was also detected, to a correspondingly lesser extent, in vesicular glutamate transporter 2 (vGlut2) mRNA-containing neurons in MS and DB ( 13% and 5% co-expression, respectively). Similarly, a qualitative assessment of the MS/DB region, identified Rxfp3 mRNA in neurons that expressed parvalbumin (PV) mRNA (reflecting hippocampally-projecting GABA neurons), whereas choline acetyltransferase mRNA-positive (acetylcholine) neurons lacked Rxfp3 mRNA. These data are consistent with a qualitative immunohistochemical analysis that revealed relaxin-3-immunoreactive nerve fibers in close apposition with PV-immunoreactive neurons in the MS/DB. Together these studies suggest relaxin-3/RXFP3 signaling in the MS/DB plays a role in modulating specific learning and long-term memory associated behaviors in adult mice via effects on GABAergic neuron populations known for their involvement in modulating hippocampal theta rhythm and associated cognitive processes.